Pathology and clinicopathology of buffalo against trickle infection with Fasciola gigantica - Wiedosari, Ening (Indonesian Journal of Animal and Veterinary Sciences, 1998)
Eleven male buffalo calves were divided into infected group of 7 animals and non-infected control group of 4 animals. The infected group was then inoculated with trickle doses of 15 Inetacercariae of Fasciola gigantica twice weekly for 32 weeks and killed 36 weeks after first infection. There were no clinical symptoms observed . Infected and non-infected buffaloes, had similar values of packed cell volume, haemoglobin and red blood cell counts . In infected buffaloes, plasma glutamate dehydrogenase enzyme activity increased in proportion to the dregree of hepatocyte destruction level and evidence of necrosis caused by the migrating of immature flukes through the parenchyma prior to their entry into the bile ducts. While the values of plasma glutamyl transpeptidase showed only a minimal rise with a small peak in week 20 as evidenced by histological observation that infected caused limited damage to epithelial surface of the bile duct . These results indicates that, the resistance mechaninisms of buffalo against fasciolosis infection occurred in the liver or before flukes entering into the bile ducts. These results seem to indicate that, in buffalo, resistance mechanisms to fasciolosis infection occured in the liver or before flukes entry into the bile ducts. Â  Key words: Fasciola gigantica, clinicopathology, buffalo calves, trickle infection, resistance